2013
DOI: 10.2147/ijn.s39426
|View full text |Cite
|
Sign up to set email alerts
|

Subacute toxicity of cadmium on hepatocytes and nephrocytes in the rat could be considered as a green biosynthesis of nanoparticles

Abstract: Abstract:The purpose was to study the toxicity of cadmium (Cd) and to explore its potential to generate nanoparticles during detoxification. In order to demonstrate this, in vivo fluorescence imaging, X-ray diffraction, and flow cytometry were performed. The in vivo imaging showed a fluorescence signal after Cd treatment (CdCl2, 1.50 mg/Kg, intraperitoneally). By contrast, the control-rat fluorescence was negative. The fluorescence was divided into three colors, red, yellow, and green, and probably indicates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 45 publications
(54 reference statements)
0
23
0
Order By: Relevance
“…Interestingly, fluorescence microscopy images show that co-treatment (Cd + Se group) induced a localized red fluorescence signal. 17 The superposition of fluorescence images and light microscopy images showed that fluorescence was localized in the glomeruli and renal tubules as shown in Figure 2E …”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Interestingly, fluorescence microscopy images show that co-treatment (Cd + Se group) induced a localized red fluorescence signal. 17 The superposition of fluorescence images and light microscopy images showed that fluorescence was localized in the glomeruli and renal tubules as shown in Figure 2E …”
Section: Discussionmentioning
confidence: 95%
“…Cd ions are bound by MTs via thiol groups of cysteine residues leading to Cd-MT complexes; 2,3,[25][26][27][28][29] then from the liver the Cd ions circulate in blood bound to MTs until reaching the kidneys. 7,17,30 The Cd-MT complex is easily filtered through the glomerular membrane and taken up by renal tubular cells. MTs are then catabolized, releasing Cd ions in the cytoplasm where they induce the synthesis of new MT molecules.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations